Child Marriage in Bangladesh Due to The Result of Gender Inequality and Poverty: A Detrimental Issue to Society - Karim, Mehnaz (British Journal of Healthcare and Medical Research, 2024)
Child marriage, considering the girls under eighteen, is a substantial problem faced by many young girls each year. Even though child marriage is habitually accomplished to protect the physical security of young girls, marriage at these ages can posture various intimidations to their lives, wellbeing, and upcoming visions. In this journal I have focused the reasons and impact of child marriage in Bangladesh, while considered our social and economic aspect. Even though Bangladesh is a developing country, it has the eastern cultural impact as it is a part of south-east Asia. This piece of writing will present the demographic picture along with analysis, how the gender inequality, poverty, and social demand became a detrimental issue to the lives of young girls of Bangladesh.